Высокодобротные сверхпроводящие резонансные системы СВЧ диапазона - Артеменко С. Н. Сергей Николаевич; Каминский В. Л. Валерий Людвигович; Самойленко Г. М. Геннадий Михайлович; Юшков Ю. Г. Юрий Георгиевич (1991, 1991)
В фонде НТБ ТПУ отсутствует